Accurate Phylogenetic Relationships Among Mycobacterium bovis Strains Circulating in France Based on Whole Genome Sequencing and Single Nucleotide Polymorphism Analysis - Hauer, Amandine; Michelet, Lorraine; Cochard, Thierry; Branger, Maxime; Nunez, Javier; Boschiroli, Maria-Laura; Biet, Franck (Frontiers in Microbiology, 2019)
In recent years the diversity of the French Mycobacterium bovis population responsible for bovine tuberculosis (bTB) outbreaks since 1970 has been described in detail. To further understand bTB evolution in France, we used Single Nucleotide Polymorphisms (SNP) based on whole genome sequence versus classical genotyping methods in order to identify accurate phylogenetic relationships between M. bovis strains. Whole genome sequencing was carried out on a selection of 87 strains which reflect the French M. bovis population’s genetic diversity. Sequences were compared to the M. bovis reference genome AF2221/97. Comparison among the 87 genomes revealed 9,170 sites where at least one strain shows a SNP with respect to the reference genome; 1,172 are intergenic and 7,998 in coding sequences, of which 2,880 are synonymous and 5,118 non-synonymous. SNP-based phylogenetic analysis using these 9,170 SNP is congruent with the cluster defined by spoligotyping and MLVA typing. In addition, some SNPs were identified as specific to genotypic groups. These findings suggest new SNP targets that can be used for the development of high-resolving methods for genotyping as well as for studying M. bovis evolution and transmission patterns. The detection of non-synonymous SNPs on virulence genes enabled us to distinguish different clusters. Our results seem to indicate that genetically differentiated clusters could also display distinctive phenotypic traits.